Respuesta :

Answer:

C'(1, 2 )

Step-by-step explanation:

The translation (x + 3, y - 2 ) means add 3 to the original x- coordinate and subtract 2 from the original y- coordinate, thus

C(- 2, 4 ) → C'(- 2 + 3, 4 - 2 ) → C'(1, 2 )

Answer:

C = ( 1 , 2 )

Step-by-step explanation:

original : C =  ( -2 , 4 )

formula : ( x+3 , y-2 )

( -2 + 3 ) , ( 4 - 2 )

C = ( 1 , 2 )

ill answer the other 3 as well :)  

original : A = ( -6 , 2 )

formula : ( x+3 , y-2 )

( -6 + 3 ) , ( 2 - 2 )

A = ( -3 , 0 )

___________________

original : B = ( -5 , 4 )

formula : ( x+3 , y-2 )

( -5 + 3 ) , ( 4 - 2 )

B = ( -2 , 2 )

___________________

original : D = ( 1 , 2 )

formula : ( x+3 , y-2 )

( 1 + 3 ) , ( 2 - 2 )

D = ( 4 , 0 )

yw :)

ACCESS MORE